Numerical modeling of two-phase flashing propellant flow inside the twin-orifice system of pressurized metered dose inhalers - Abdul Qaiyum Shaik (2010)
Pressurized metered-dose inhalers (pMDIs) are the most widely-prescribed inhaler devices for therapeutic aerosol delivery in the treatment of lung diseases. In spite of its undoubted therapeutic and commercial success, the propellant flow mechanics and aerosol formation by the pMDIs is poorly understood. The process involves a complex transient cavitating turbulent fluid that flashes into rapidly evaporating droplets, but details remain elusive, partly due to the difficulty of performing experiments at the small length scales and short time scales. The objective of the current work is the development of a numerical model to predict the internal flow conditions (pressure, temperature, velocity, void fraction, quality, etc.) and provide deeper insight into the atomization process and fluid mechanics involved in the twin-orifice of pMDIs. The main focus is propellant metastability, which has been identified by several past authors as a key element that is missing in accounts of pMDI performance. First the flashing propellant flow through single orifice systems (both long and short capillary tubes) was investigated using three different models : homogeneous equilibrium model (HEM), delayed equilibrium model (DEM) and improved delayed equilibrium model (IDEM). Both, the pure propellants and the propellant mixtures were used as working fluid. The numerical results were compared with the experimental data. For long capillary tubes the three models gave reasonable predictions, but the present results showed that DEM predicts the mass flow rate well for pure propellants and IDEM predicts the mass flow rate well for propellant mixtures. For short capillary tubes, the present results showed that DEM predicts the mass flow rate and pressure distribution along the short tube better compared to HEM and IDEM. The geometry of the twin-orifice system of a pMDI is complex and involves several singularities (sudden enlargements and sudden contractions). Various assumptions were made to evaluate their effect on the vaporisation process and to evaluate the flow variables after the shock at the exit of the spray orifice when the flow is choked. Also, three different propellant flow regimes were explored at the inlet of the valve orifice. A specific combination of assumptions, which offers good agreement with the experimental data was selected for further computations. Numerical investigations were carried out using delayed equilibrium model (DEM) with these new assumptions to validate the two-phase metastable flow through twin-orifice systems with continuous flows of various propellants studied previously by Fletcher (1975) and Clark (1991). A new correlation was developed for the coefficient in the relaxation equation. Along with this correlation a constant coefficient was used in the relaxation equation to model the metastability. Both the coefficients showed good agreement against the Fletcher's experimental data. The comparison with the Clark s experimental data showed that the new correlation coefficient predicted the mass flow rate well in compare to that of the constant coefficient, but over predicted the expansion chamber pressure. The DEM with both the coefficients for continuous discharge flows were applied to investigate the quasi-steady flashing flow inside the metered discharge flows at various time instants. The DEM results were compared with the Clark s metered discharge experimental data and the well established homogeneous equilibrium model (HEM). The comparison between the HEM and DEM with Clark s (1991) experimental data showed that the DEM predicted the mass flow well in compare to that of HEM. Moreover, both the models underpredicted the expansion chamber pressure and temperature. The findings of the present thesis have given a better understanding of the role played by the propellant metastability inside the twin-orifice system of pMDIs. Also, these have provided detailed knowledge of thermodynamic state, void fraction and critical velocity of the propellant at the spray orifice exit, which are essential step towards the development of improved atomisation models. Improved understanding of the fluid mechanics of pMDIs will contribute to the development of next-generation pMDI devices with higher treatment efficacy, capable of delivering a wider range of therapeutic agents including novel therapies based around.